2023
DOI: 10.1002/smll.202207044
|View full text |Cite
|
Sign up to set email alerts
|

Monodispersed Pt Sites Supported on NiFe‐LDH from Synchronous Anchoring and Reduction for High Efficiency Overall Water Splitting

Abstract: Precise design of low‐cost, efficient and definite electrocatalysts is the key to sustainable renewable energy. Herein, this work develops a targeted‐anchored and subsequent spontaneous‐redox strategy to synthesize nickel‐iron layered double hydroxide (LDH) nanosheets anchored with monodispersed platinum (Pt) sites (Pt@LDH). Intermediate metal‐organic frameworks (MOF)/LDH heterostructure not only provides numerous confine points to guarantee the stability of Pt sites, but also excites the spontaneous reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…[31] The Fe 2p 3/2 signals of Mo-FeNi LDH and FeNi-LDH split into two peaks, of which the peak at 708.1 eV was attributed to the Fe III oxidation state. [32] The peak at 712.1 eV that was assigned to the Fe II spectrum exhibited a slight shift of 0.2 eV to lower binding energies, confirming that the electronic configuration had changed after the introduction of Mo metal ions. Two typical peaks appeared around 855.6 and 873.4 eV in the Ni 2p spectra can be attributed to Ni 2p 3/2 and Ni 2p 1/2 , [33] respectively.…”
Section: Resultsmentioning
confidence: 85%
“…[31] The Fe 2p 3/2 signals of Mo-FeNi LDH and FeNi-LDH split into two peaks, of which the peak at 708.1 eV was attributed to the Fe III oxidation state. [32] The peak at 712.1 eV that was assigned to the Fe II spectrum exhibited a slight shift of 0.2 eV to lower binding energies, confirming that the electronic configuration had changed after the introduction of Mo metal ions. Two typical peaks appeared around 855.6 and 873.4 eV in the Ni 2p spectra can be attributed to Ni 2p 3/2 and Ni 2p 1/2 , [33] respectively.…”
Section: Resultsmentioning
confidence: 85%
“…Recent research has indicated that the type and quantity of defects significantly impact the catalytic activity of crystalline material catalysts. [37][38][39] Although crystal defects play a crucial role in catalytic materials, their diversity and complex nature make their study challenging. Consequently, a systematic review of defective state catalysts is necessary to facilitate an improved comprehension and design of catalysts.…”
Section: Innovative Strategies To Improve Oer Performancesmentioning
confidence: 99%
“…Compared with the fear of complex and fine regulation of semiconductor catalysts, exploring alternative traditional semiconductor photocatalysts may be a feasible strategy. Layered double hydroxide (LDH), as a promising photocatalyst, has been extensively studied in CO 2 photoreduction systems owing to its tunable electronic structure and band gap ( E g ), unique layered structure, low cost, ease of scale-up, and the fact that it is expected to be able to replace TiO 2 , etc., traditional semiconductors. Some preliminary studies have also revealed that specific co-catalysts (e.g., Pt, Pd) can facilitate electron transfer and separation efficiency during the reaction. However, the integration of the three elements (high CO 2 adsorption capacity, light capture capacity, and rapid separation of photogenerated charges) of photocatalysis into one LDH-based photocatalyst is still rarely reported.…”
Section: Introductionmentioning
confidence: 99%